ANALISIS iiPERAN iiDAN iiFUNGSI iiBUMDES iiDALAM iiMENYEJAHTERAKAN MASYARAKAT iiDESA NGARAK iiKECAMATAN iiMANDOR KABUPATEN iiLANDAK - NIM. A1011211048, ARTINI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract BUMDes ii(Village-Owned iiEnterprises) iiare iivillage-owned iibusinesses iiwhose iicapital iicomes iifrom iivillage iiassets iito iimanage iiassets, iiservices iiand iibusinesses iifor iithe iiwelfare iiof iithe iicommunity. iiIn iiNgarak iiVillage, iithe iionly iiprogram iirunning iiis iithe iiPond iiBusiness iiUnit, iiwhich iiis iimanaged iiby iiBUMDes iiadministrators iiand iiland iiowners. iiThey iiare iiresponsible iifor iibreeding, imaintaining, harvesting iiand iiselling iifish. iiHowever, iiafter iialmost iitwo iiyears iiof iioperation, iithe iivillage iihas iinot iifelt iithe iibenefits. iiLack iiof iifunds iicauses iimanagers iiand iiworkers iito iiquit, iiresulting iiin iiBUMDes iibecoming iia iivacuum. iiApart iifrom iithat, iithe iimanagement iihas iinot iibeen iiable iito iicarry iiout iiits iiduties iioptimally. iiThis iithesis iiaims iito iiexamine iithe iirole iiand iifunction iiof iiBUMDes iiin iiimproving iithe iiwelfare iiof iithe iipeople iiof iiNgarak iiVillage, iiconsidering iithat iiBUMDes iiis iistill iirelatively iinew iiin iiMandor iiDistrict, iiand iimany iiparties iistill iido iinot iiunderstand iiit. This iiresearch iiuses iia iisociological iijuridical iimethod, iinamely iian iiapproach iibased iion iiapplicable iinorms iior iiregulations iito iiunderstand iiits iiimpact iion iisocial iilife. iiThis iiresearch iiis iidescriptive, iiwhich iimeans iiit iidescribes iiand iiexplains iifacts iisystematically. iiData iiwas iicollected iithrough iiobservation ii(direct iiobservation iiin iithe iifield), iidocument iistudy ii(searching iihistorical iidata), iiand iiinterviews ii(extracting iiinformation iifrom iisources). iiThis iiresearch iiis iisupported iiby iiplanning iitheory iiand iimonitoring iitheory. The iiresearch iiresults iishow iithat iithe iirole iiand iifunction iiof iiBUMDes iiin iiimproving iithe iiwelfare iiof iithe iicommunity iiin iiNgarak iiVillage, iiMandor iiDistrict, iiLandak iiRegency iihas iinot iigone iias iiexpected. iiThis iican iibe iiseen iifrom iithe iiprograms iicarried iiout. iiThe iiprogram iihas iinot iirun iioptimally iidue iito iicapital iiconstraints, iiweather iifactors, iiand iithe iiBUMDes iimanagement iiand iithe iiVillage iiGovernment's iilack iiof iiunderstanding iiof iithe iiBUMDes iithey iimanage. iiSo iiin iicarrying iiout iithe iirole iiand iifunction iiof iiBUMDes iiwith iithe iiaim iiof iiimproving iithe iiwelfare iiof iithe iiNgarak iivillage iicommunity, iiit iihas iistill iinot iibeen iiachieved. Keywords: iiPlanning; iiImplementation; iiSupervision; iiRole iiand iiFunction iiof iiBUMDes iiin iiProspering iiSociet Abstrak BUMDes ii(Badan iiUsaha iiMilik iiDesa) iiadalah iiusaha iimilik iidesa iiyang iimodalnya iiberasal iidari iikekayaan iidesa iiuntuk iimengelola iiaset, iijasa, iidan iiusaha iidemi iikesejahteraan iimasyarakat. iiDi iiDesa iiNgarak, iisatu-satunya iiprogram iiyang iiberjalan iiadalah iiUnit iiUsaha iiKolam, iiyang iidikelola iioleh iipengurus iiBUMDes iidan iipemilik iilahan. iiMereka iibertanggung iijawab iiatas iipembibitan, iipemeliharaan, iihingga iipanen iidan iipenjualan iiikan. iiNamun, iisetelah iihampir iidua iitahun iiberjalan, iidesa iibelum iimerasakan iimanfaatnya. iiKurangnya iidana iimenyebabkan iipengelola iidan iipekerja iiberhenti, iisehingga iiBUMDes iimenjadi iivakum. iiSelain iiitu, iipengurus iibelum iimampu iimenjalankan iitugasnya iisecara iioptimal. iiSkripsi iiini iibertujuan iiuntuk iimengkaji iiperan iidan iifungsi iiBUMDes iidalam iimeningkatkan iikesejahteraan iimasyarakat iiDesa iiNgarak, iimengingat iiBUMDes iimasih iitergolong iibaru iidi iiKecamatan iiMandor, iidan iibanyak iipihak iimasih iibelum iimemahaminya. Ii Penelitian iiini iimenggunakan iimetode iiyuridis iisosiologis, iiyaitu iipendekatan iiberdasarkan iinorma iiatau iiperaturan iiyang iiberlaku iiuntuk iimemahami iidampaknya iidalam iikehidupan iisosial. iiPenelitian iiini iibersifat iideskriptif, iiyang iiberarti iimenggambarkan iidan iimenjelaskan iifakta iisecara iisistematis. iiData iidikumpulkan iimelalui iiobservasi ii(pengamatan iilangsung iidi iilapangan), iistudi iidokumen ii(penelusuran iidata iihistoris), iidan iiwawancara ii(penggalian iiinformasi iidari iinarasumber). iiPenelitian iiini iididukung iioleh iiteori iiperencanaan iidan iiteori iipengawasan. Hasil iipenelitian iimenunjukan iibahwa iiperan iidan iifungsi iiBUMDes iidalam iimenyejahterakan iimasyarakat iidi iiDesa iiNgarak iiKecamatan iiMandor iiKabupaten iiLandak iibelum iiberjalan iisesuai iidengan iiyang iidiharapkan. iiHal iiini iidapat iidilihat iidari iiprogram iiyang iidikerjakan. iiProgram iitersebut iibelum iiberjalan iidengan iimaksimal iikarena iikendala iimodal, iifaktor iicuaca, iiserta iiketidak iipaham iipengurus iiBUMDes iiserta iiPemerintah iiDesa iiterhadap iiBUMDes iiyang iidi iikelola. iiSehingga iidalam iimenjalankan iiperan iidan iifungsi iiBUMDes iidengan iitujuan iiuntuk iimenyejahterakan iimasyarakat iidesa iiNgarak iimasih iibelum iitercapai. ii Kata iiKunci ii: iiPerencanaan; iiPelaksanaan; iiPengawasan; iiPeran iidan iiFungsi iiBUMDes iidalam iiMenyejahterakan iiMasyarakat.